Revision of the Japanese Ablabesmyia (Diptera: Chironomidae: Tanypodinae), with descriptions of three new species - Niitsuma, Hiromi (Zootaxa, 2013)
The Japanese species of Ablabesmyia Johannsen are reviewed on the basis of the type material and the specimens obtained recently. Four species of the subgenus Ablabesmyia, A. (A.) monilis (Linnaeus), A. (A.) amamisimplex Sasa, A. (A.) jogan-cornua Sasa et Okazawa and A. (A.) prorasha Kobayashi et Kubota, are recognized as valid. The adults, male and female, and the immature stages, pupa and larva, of the first species and the adult males of the remaining are redescribed, while the female adults and both immature stages of A. (A.) amamisimplex and A. (A.) jogancornua, and both immature stages of A. (A.) prorasha are described here for the first time. Reexamination of the holotypes of A. (A.) amamisimplex and A. (A.) jogancornua has shown that the respective original descriptions contain errors in some diagnostic aspects, which are corrected in this study. In addition, the male and female adults, pupa and larva of a new species of the subgenus Karelia Roback, A. (K.) makarchenkoi n. sp., and the male adults of two new species, A. (K.) lata n. sp. and A. (K.) perexilis n. sp., are described and illustrated.